2011
DOI: 10.1007/s12646-011-0087-9
|View full text |Cite
|
Sign up to set email alerts
|

In the Eye of the Beholder: Alcohol Use and Perceptions Among Student-Patrons of ‘Joints’ in Three Nigerian University Communities

Abstract: Alcohol use and its associated problems among university students have attracted empirical investigation by researchers and scholars. While many of these studies have reported a very high level of alcohol consumption and highlighted the various problems this portends, alcoholrelated perceptions of this vulnerable population, which could be germane to intervention aimed at curtailing the problem, have remained largely under-researched. This cross-sectional survey examined the use and perceptions of alcohol by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In contemporary Nigeria, available quantitative studies reveal that many young men are drinking hazardously and are using other substances [53,54]. Among their female counterparts, a few studies [55,56] have identified different patterns of alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…In contemporary Nigeria, available quantitative studies reveal that many young men are drinking hazardously and are using other substances [53,54]. Among their female counterparts, a few studies [55,56] have identified different patterns of alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…He adopted a 93-item questionnaire that combined ''six mutually exclusive scales'' to measure risky behaviours due to harmful alcohol use. Abikoye and Osinowo (2011) in another survey of 1705, purposively selected students of three universities in western Nigeria; they adopted the AUDIT questionnaire to measure the perception of students who patronize drinking joints. Chikere and Mayowa (2011) also employed self-administered structured questionnaire to describe the prevalence and perceived health effect of alcohol use among 482 male undergraduate students in Owerri, eastern Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…For example, two studies (Abikoye and Osinowo 2011;Chikere and Mayowa 2011) reported that students use alcohol to enhance sexual performance. This finding is a sensitive one attributable to myriad of reasons, one such is how some alcoholic beverages are advertised in Nigeria (Obot and Ibanga 2002).…”
Section: Discussion and Conclusion The Necessities Of Mixed Methods Dmentioning
confidence: 99%
“…It was important to explore the social context of drinking amongst young people who lived on and around University campus as these locations are key sites for excessive alcohol consumption in Nigeria [ 30 ]. This study was conducted on a university located in a city of Anambra State, south-eastern Nigeria between September and December 2013.…”
Section: Methodsmentioning
confidence: 99%
“…to construct/express a range of masculine/feminine identities) [ 29 ]. There is also evidence of diverse drinking patterns and motives among students in Nigeria [ 30 , 31 ] and alcohol-related problems such as accidents, mental disorder, anxiety, amongst others, are increasing [ 32–34 ] but to date, there is no empirical evidence on how the media may be part of these trajectories.…”
Section: Introductionmentioning
confidence: 99%